Investigating smoke optical properties in Eastern Mediterranean: Lidar observations in Cyprus - Poutli, Maria; Mamouri, Rodanthi-Elisavet; Nisantzi, Argyro; Michailidis, Konstantinos; Prodromou, Maria; Hadjimitsis, Diofantos G. (My University, 2025)
Wildfires are large, uncontrolled fires that often occur in rural or sparsely populated areas. The main causes of wildfires can be attributed to either human activity or natural factors. When key conditions such as heat, drought, and fuel availability reach critical thresholds, wildfires can ignite or become more intense. Climate change affects these parameters by lowering the critical values required for fire activity to occur [1]. The IPCC (AR6) states with medium confidence that weather conditions favoring wildfires have become more probable in southern Europe, northern Eurasia, the USA, and Australia over the last century [2]. Smoke particles play a significant role in the climate system, affecting it directly by absorbing solar radiation and indirectly by influencing cloud formation as cloud condensation nuclei (CCN) and icenucleating particles (INPs) [3]. They also impact air quality, visibility, and pose health risks. Studying their optical properties is essential for understanding their role in the climate system and improving weather and climate models. The Mediterranean region is a key area for atmospheric studies due to the diverse aerosol types it experiences. Cyprus, the third-largest island in the Mediterranean, provides a strategic location for investigating the vertical distribution of aerosols, including marine particles, desert dust, smoke, and anthropogenic particles. Hence, this is a great opportunity to study the behavior of smoke in such aerosol mixtures. This study emphasizes on the intense activity of wildfires in Turkey's Mediterranean Region in July and August 2021, and the corresponding smoke layers that were observed above Limassol site.